2022
DOI: 10.3390/antibiotics11081015
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Eradicate Carbapenem-Resistant Acinetobacter baumannii (CRAB) from Endemic Hospitals?

Abstract: Background: Despite the global efforts to antagonize carbapenem-resistant Acinetobacter baumannii (CRAB) spreading, it remains an emerging threat with a related mortality exceeding 40% among critically ill patients. The purpose of this review is to provide evidence concerning the best infection prevention and control (IPC) strategies to fight CRAB spreading in endemic hospitals. Methods: The study was a critical review of the literature aiming to evaluate all available studies reporting IPC measures to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…Control of CRAB infections in endemic hospitals remains a challenge. In addition to hand hygiene as a core component of infection prevention and control, active surveillance cultures, contact precautions, cohorting patients, environmental disinfection, use of chlorhexidine baths, and closing or stopping admissions to the ward have been adopted to eradicate CRAB infections from endemic hospitals, as illustrated in a recent review [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Control of CRAB infections in endemic hospitals remains a challenge. In addition to hand hygiene as a core component of infection prevention and control, active surveillance cultures, contact precautions, cohorting patients, environmental disinfection, use of chlorhexidine baths, and closing or stopping admissions to the ward have been adopted to eradicate CRAB infections from endemic hospitals, as illustrated in a recent review [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, several IPC measures have been recommended to manage CRAB outbreaks in the ICU. A recent review of 12 studies conducted over the last 10 years in settings where CRAB transmission is both epidemic and endemic found wide variability in the frequency of application of IPC measures ( 28 ). While all studies adopted a multimodal approach, the most frequently applied strategies (75 to 100% of studies) resulted in environmental disinfection, contact precautions, and cohorting of staff and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Infections included about 8500 cases of nosocomial infection, and as many as 700 such deaths were related to antibiotic resistance [ 13 ]. Multiple studies revealed that carbapenem-resistant A. baumannii isolates were frequently isolated among patients with pneumonia, followed by patients with bloodstream infections and urinary tract infections, particularly in the intensive care unit (ICU) [ 14 , 15 , 16 ]. The prevalence of carbapenem-resistant A. baumannii varies between 30% in USA and 94% in Greece [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies revealed that carbapenem-resistant A. baumannii isolates were frequently isolated among patients with pneumonia, followed by patients with bloodstream infections and urinary tract infections, particularly in the intensive care unit (ICU) [ 14 , 15 , 16 ]. The prevalence of carbapenem-resistant A. baumannii varies between 30% in USA and 94% in Greece [ 16 ]. A multicenter study in Indonesia reported that the prevalence of carbapenem-resistant A. baumannii bloodstream infections increased from 49% in 2016 to 57% in 2018 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation